Modelling Conditional Probability Densities for Periodic Variables - Bishop, Christopher; Nabney, Ian T. (Mathematics of Neural Networks: Models, Algorithms and Applications, 1997)
Most conventional techniques for estimating conditional probability densities are inappropriate for applications involving periodic variables. In this paper we introduce three related techniques for tackling such problems, and test them using synthetic data. We then apply them to the problem of extracting the distribution of wind vector directions from radar scatterometer data.